Temporal dynamics and molecular characterization of acetic acid bacteria during palm vinegar (Arenga pinnata) fermentation - RASTINA RASTINA; SAFIKA SAFIKA; ZINATUL HAYATI; WINDA YULIA; DARMAWI DARMAWI (Society for Indonesian Biodiversity, 2026)
Abstract. Rastina, Safika, Hayati Z, Yulia W, Darmawi. 2026. Temporal dynamics and molecular characterization of acetic acid bacteria during palm vinegar (Arenga pinnata) fermentation. Biodiversitas 27 (7): d270708. https://doi.org/10.13057/biodiv/d270708. Palm vinegar is a traditional fermented product whose quality depends on the ecological succession and metabolic activity of Acetic Acid Bacteria (AAB). This study evaluated the temporal dynamics of AAB populations and titratable acidity during spontaneous fermentation of Arenga pinnata palm sap from Aceh Besar, Indonesia, and identified a dominant isolate using phenotypic and molecular approaches. Fermentation samples were analyzed on days 3, 6, 9, 12, and 15 using culture-based enumeration, titratable acidity measurement, phenotypic characterization, PCR amplification of the 16S rRNA gene, sequencing, and phylogenetic analysis. AAB counts increased from 6.08 ± 0.04 log CFU/mL on day 3 to a maximum of 8.94 ± 0.03 log CFU/mL on day 12, followed by a slight decline on day 15. Titratable acidity showed a similar temporal pattern, increasing from 1.33 ± 0.40% on day 3 to a maximum value on day 12 before decreasing on day 15. One-way ANOVA indicated that fermentation time significantly influenced both AAB counts and titratable acidity (P < 0.05). The selected isolate, B2, showed phenotypic characteristics consistent with AAB, including Gram-negative staining, catalase activity, and halo formation on calcium carbonate-containing medium. Sequence-based identification placed isolate B2 within the Acetobacter group with 99.85% sequence identity. These findings suggest that day 12 represents a critical stage of active acetification under the conditions examined. The study provides preliminary culture-based and molecular information on AAB dynamics in traditional palm vinegar fermentation, while highlighting the need for broader community-level analysis and replicate sampling to better characterize microbial biodiversity.